The Awakening of Sunshine Girl (The Haunting of Sunshine Girl Book 2) - McKenzie, Paige; Sheinmel, Alyssa B.; Hagen, Nick (New York, NY Weinstein Books, 2016)
"Sunshine Griffith can communicate with ghosts. Even more amazing, she recently discovered--with the help of her would-be boyfriend Nolan--that's she's a luiseach, one of an ancient race of creatures who have lived among humans for centuries, protecting them from dark spirits and helping them move on to the afterlife. Now, Sunshine's powers are awakening and she feels spirits everywhere--intense and sometimes overwhelming. Eager to get her supernatural abilities under control, Sunshine agrees to begin training with her mentor, her estranged father Aidan"--Dust jacket flap.
Keywords: Teenage girls -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Family secrets -- Juvenile fiction; Paranormal fiction; Horror tales; Teenage girls -- Fiction; Fathers and daughters -- Fiction; Secrets -- Fiction; Families -- Fiction; Supernatural -- Fiction; Horror stories